2019
DOI: 10.1186/s12933-019-0965-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in lipid metabolism between anagliptin and sitagliptin in patients with type 2 diabetes on statin therapy: a secondary analysis of the REASON trial

Abstract: Background: Anagliptin, a dipeptidyl peptidase-4 inhibitor, is reported to reduce the level of low-density lipoprotein cholesterol (LDL-C). The underlying mechanism of this effect and effect on lipid metabolism however remains uncertain. Aim and methods:We therefore evaluate the effects of anagliptin on lipid metabolism-related markers compared with those of sitagliptin. The study was a secondary analysis using data obtained from the Randomized Evaluation of Anagliptin versus Sitagliptin On low-density lipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In a human study using a small number of drug-naïve patients with type 2 diabetes and LDL-C > 120 mg/dL (n = 30), anagliptin significantly decreased a cholesterol synthesis marker, lathosterol, without affecting cholesterol absorption markers including campesterol, sitosterol and cholestanol [45]. Furthermore, a previous sub-analysis using data from the REASON trial demonstrated that anagliptin reduced LDL-C level by suppressing excess cholesterol synthesis even when it was used in combination with statin therapy [46]. Taken together, these findings suggest that anagliptin exerts a hepatoprotective effect beyond its glycemic-lowering action.…”
Section: Possible Mechanisms Of Reduction In Fabp4 Concentration By Anagliptinmentioning
confidence: 92%
“…In a human study using a small number of drug-naïve patients with type 2 diabetes and LDL-C > 120 mg/dL (n = 30), anagliptin significantly decreased a cholesterol synthesis marker, lathosterol, without affecting cholesterol absorption markers including campesterol, sitosterol and cholestanol [45]. Furthermore, a previous sub-analysis using data from the REASON trial demonstrated that anagliptin reduced LDL-C level by suppressing excess cholesterol synthesis even when it was used in combination with statin therapy [46]. Taken together, these findings suggest that anagliptin exerts a hepatoprotective effect beyond its glycemic-lowering action.…”
Section: Possible Mechanisms Of Reduction In Fabp4 Concentration By Anagliptinmentioning
confidence: 92%
“…Most of the study patients 2 (SREBP2) in the liver 30) and inhibits absorption of cholesterol in the small intestine 31) . In human studies, it has been shown that inhibition of cholesterol synthesis 32) and suppression of excess cholesterol synthesis 33) are possible mechanisms for LDL-C reduction by anagliptin. On the other hand, the precise mechanisms by which anagliptin, but not sitagliptin, suppresses an excess increase in circulating PCSK9 level in patients receiving statin therapy are unclear.…”
Section: Correlation and Multivariable Linear Regression Analyses Formentioning
confidence: 99%
“…It has been reported that circulating PCSK9 has a diurnal rhythm synchronous with cholesterol synthesis marker lathosterol 34) . Inhibition of cholesterol synthesis 32) and suppression of excess cholesterol synthesis 33) by anagliptin may be linked to reduced PCSK9 levels. In addition, statin therapy is significantly associated with a compensatory increase in plasma PCSK9 concentration 24) .…”
Section: Correlation and Multivariable Linear Regression Analyses Formentioning
confidence: 99%
“…Both sitagliptin and anagliptin are being evaluated in clinical trials for their potential in the regulation of lipid metabolism and CVD in T2DM patients ( Table 2 ). Anagliptin has been shown to decrease LDL-C triglycerides, total cholesterol, and non-HDL-C levels in a mechanism independent from its hypoglycemic effects [ 59 ]. Other gliptins increase adiponectin levels and reduce intestinal cholesterol absorption [ 18 ].…”
Section: Therapies Based On the Incretin Systemmentioning
confidence: 99%